2022
DOI: 10.1038/s41525-021-00271-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal microarray analysis of 410 Han Chinese patients with autism spectrum disorder or unexplained intellectual disability and developmental delay

Abstract: Copy number variants (CNVs) are recognized as a crucial genetic cause of neurodevelopmental disorders (NDDs). Chromosomal microarray analysis (CMA), the first-tier diagnostic test for individuals with NDDs, has been utilized to detect CNVs in clinical practice, but most reports are still from populations of European ancestry. To contribute more worldwide clinical genomics data, we investigated the genetic etiology of 410 Han Chinese patients with NDDs (151 with autism and 259 with unexplained intellectual disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Our diagnostic yield (37.18%) is quite high compared to the estimated 15–20% yield of CMA methods, albeit these estimates are often based on studies where selection criteria were rather broad and CMA resolution was relatively low [ 2 ]. Our diagnostic yield is comparable to several studies with smaller patient groups and/or similarly strict selection criteria [ 5 15 ].…”
Section: Discussionsupporting
confidence: 79%
“…Our diagnostic yield (37.18%) is quite high compared to the estimated 15–20% yield of CMA methods, albeit these estimates are often based on studies where selection criteria were rather broad and CMA resolution was relatively low [ 2 ]. Our diagnostic yield is comparable to several studies with smaller patient groups and/or similarly strict selection criteria [ 5 15 ].…”
Section: Discussionsupporting
confidence: 79%
“…We found a diagnostic rate of only CMA analysis as 21% presenting 8 pathogenic/likely pathogenic CNVs. In the previous studies including CMA analysis, CNVs were found in the range of 5-35% of the patients, depending on the DD/ID patient selection criteria and classification of detected variants [Miller et al, 2010;Gürkan et al, 2020;Liu et al, 2022]. In our study, we found that the diagnosis was mostly made by NGS methods.…”
Section: Discussionmentioning
confidence: 46%
“…28,29) Table 3 summarizes the recent studies that highlighted the genetic significance of assessing individuals with GDD/ID and NDDs. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]…”
Section: Genetic Testingmentioning
confidence: 99%